MỤC LỤC
Nguyên hàm $\Large F(x)$ trên $\Large (-\infty ;0)$ của hàm số $\Large f(x)=-\dfrac{1}{{{x}^{2}}}{{e}^{\dfrac{1}{x}}}$ thỏa mãn điều kiện $\Large F(-1)=\dfrac{1}{e}$ là:
Lời giải chi tiết:
Ta có $\Large F(x)=\int{-\dfrac{1}{{{x}^{2}}}{{e}^{\dfrac{1}{x}}}dx=\int{{{e}^{\dfrac{1}{x}}}}}d\left( \dfrac{1}{x} \right)={{e}^{\dfrac{1}{x}}}+C$
$\Large F(-1)=\dfrac{1}{e}\Leftrightarrow {{e}^{-1}}+C=\dfrac{1}{e}\Leftrightarrow C=0$
Vậy $\Large F(x)={{e}^{\dfrac{1}{x}}}$
Chọn đáp án A
Xem thêm các bài tiếp theo bên dưới